2013
DOI: 10.1002/adsc.201300201
|View full text |Cite
|
Sign up to set email alerts
|

Tetraalkynylated and Tetraalkenylated Benzenes and Pyridines: Synthesis and Photophysical Properties

Abstract: Tetra(arylalkynyl)pyridines and tetra(arylalkenyl)pyridines and their benzene analogues were prepared by palladium‐catalyzed cross‐coupling reactions from the commercially available chlorinated substrates in good to excellent yields. The photophysical properties of selected compounds were investigated and compared to each other. Very good fluorescence quantum yields were observed, especially for the pyridine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
1
27
1
Order By: Relevance
“…In the case of weak electronic couplings, the phenomenon of AIEE could be related to different effects, such as the reduction of oxygen quenching and the formation of a hydrophobic microenvironment inside the aggregate, as well as the blocking of photochemical processes such as E / Z isomerization in the excited singlet state . It is well known that styryl‐substituted benzenes undergo E / Z photoisomerizations; the Z , E , E ‐conformer of 1,3,5‐tris(styryl)benzene is less fluorescent than that of the E , E , E ‐conformer . The lower temperature and increase in the viscosity of the medium hinder this type of deactivation process associated with changes in the molecular geometry, and thus, increase the value of the fluorescence quantum yield and lifetime .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of weak electronic couplings, the phenomenon of AIEE could be related to different effects, such as the reduction of oxygen quenching and the formation of a hydrophobic microenvironment inside the aggregate, as well as the blocking of photochemical processes such as E / Z isomerization in the excited singlet state . It is well known that styryl‐substituted benzenes undergo E / Z photoisomerizations; the Z , E , E ‐conformer of 1,3,5‐tris(styryl)benzene is less fluorescent than that of the E , E , E ‐conformer . The lower temperature and increase in the viscosity of the medium hinder this type of deactivation process associated with changes in the molecular geometry, and thus, increase the value of the fluorescence quantum yield and lifetime .…”
Section: Resultsmentioning
confidence: 99%
“…[53] Different mechanisms could contribute to the nonradiative deactivation of compound 3,s uch as intramolecular charge-transfer quenching, [54][55][56] intramolecular motions that lead to ad eformation of the molecular structure in the excited state, [57] and E/Z photoisomerizations. [38,53,58,59] DFT calculations showed that the planarity of the molecular structure of 3 was slightly reduced in the S 0 !S 1 excitation process, in contrast with the planarization observed for 1 and 2 upon excitation( one or two styryl branches are significantly planarized in the case of compounds 1 and 2,r espectively,t hrough the dihedral angles t 1 and t 2 ). Figure 2p rovides as chematic representation of the mostd ramatic changes predicted in the molecular geometry upon excitation.A ccordingly,t he vibronic structure of the fluorescencee mission spectra is more clearly observedf or compounds 1 and 2 in all solvents used (see Figures 1a nd 3a nd Figure S8 in the Supporting Information);t his suggestst hat these compounds adopt am ore planar andc onjugated structure in the excited state than that of 3.…”
Section: Free Molecules In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…540–560 nm in CH 2 Cl 2 ); however, without exception, the quantum yields of 1 – 9 (0.61–0.89) are all improved compared to the values for the respective Bu 2 N‐substituted compounds (0.20–0.49), thus supporting the notion that the transitions in the BuO‐substituted TAEBs are indeed more π ‐ π *‐like in character. Nonetheless, the donor/acceptor topology of 1 – 9 does have a modest effect on the TAEB chromophore, as the closely related all MeO‐donor compound emits at 406 nm with a QY of 0.50 . This too is considerably blue‐shifted compared to the all Bu 2 N‐donor that emits at 512 nm …”
Section: Resultsmentioning
confidence: 97%
“…The 3,4,5-tribromo-2,6-dimethylpyridine 3, 3,5-dibromo-4-chloro-2,6-dimethylpyridine 8, corresponding 2,3,6-triaryl-1-methyl-1H-indoles were prepared in very good yields from both electron-rich and electron-deficient arylboronic acids in the presence of Pd[PPh 3 ] 4 in 1,4-dioxane. An efficient procedure leading to variously substituted tetra(styryl)pyridines was published by Ehlers et al 33 A highly active catalytic system based on the Buchwald ligand X-Phos [34][35][36] and PdCl 2 (CH 3 CN) enabled smooth four-fold arylation of readily available 2,3,5,6-tetrachloropyridine. Similar conditions applied to pentachloropyridine yielded a library of pentaarylpyridines with electron-deficient and electron-rich ring systems.…”
Section: Resultsmentioning
confidence: 99%